“The silent killer”: a case series on pulmonary embolisms - Sharan BOSE; P.K. ANANTHAKUMAR; K.V. RAJALAKSHMI; Jibin SIMON (Romanian Journal of Medical Practice)
Background and objectives. Pulmonary embolism (PE) is the third most common cause of death among hospitalized patients. The clinical presentation of a PE is highly variable and requires a high degree of suspicion to diagnose especially in a timely manner. A good grasp of various risk factors that may predispose a patient to a venous thromboembolism (VTE) and knowledge of the various presentations possible is required in order to diagnose and initiate potentially life-saving treatment in these patients. Here, we will look at five unique clinical presentations of a PE that highlight the variability of presentation in these cases. Materials and methods. 5 unique clinical presentations of pulmonary embolism were chosen and clinical data discussed. These cases included male and female patients of different age groups, with different risk factors and drastically different clinical presentations. The cases chosen ranged from a young male in his 20s with no risk factors presenting to us with an episode of syncope to a 62 year old diabetic female who presented with a stroke. Their different presentations, our approach to the diagnostic process and their subsequent management were emphasized. Conclusions. The spectrum of clinical presentation in a case of pulmonary embolism is very wide. A high degree of clinical suspicion is necessary to make a timely diagnosis of a PE, especially in the ER. This is especially pertinent given the fact that mortality in untreated cases is a whopping 30% compared to 8% with timely therapy. Thus it is imperative for clinicians to have a comprehensive understanding of the various presentations possible, to allow timely detection and prevent delays in the potentially lifesaving therapy that must be initiated.